Evaluation of the Measles/MR Supplemental Immunization Program for Children Under Two Years in the Palu City Health Office Working Area - Muhammad Jusman Rau; Stefiani Bengan Laba; Dilla Srikandi Syahadat; Marselina Marselina; Nur Hikmah Buchair; Nur Fadhilah Sari; Nur Azizah Azzahra (Media Publikasi Cendekia Indonesia, 2026)
Measles and rubella (MR) remain significant public health concerns in Indonesia, with outbreaks linked to low immunization coverage. A notable measles outbreak in October 2023 underscored the urgency of achieving herd immunity through high vaccination rates. The Ministry of Health targets 100% coverage for supplemental MR immunization; however, in 2022 Central Sulawesi reached only 30.4%, and in 2024 Palu City recorded 57.8%, both far below the target. This study aimed to evaluate the implementation of the measles/MR supplemental immunization program in 14 CHCs under the Palu City Health Office. A descriptive, quantitative, evaluative approach was employed to identify the program's strengths and weaknesses, which were assessed across input, process, and output dimensions using questionnaires. Regarding input, 100% of the CHCs had immunization officers with relevant educational qualifications, and 93% had received immunization-specific training. The process showed high compliance with SOP documentation: 100% of CHCs recorded vaccine temperature, inflow/outflow, and calculated remaining stock at every issuance, while 93% maintained individual stock cards, documented VVM status, and recorded equipment such as needles, syringes, and cold chain devices by type and quantity. However, only 86% recorded immunization logistics in general logbooks. The output showed that 86% of CHCs failed to meet the 100% immunization coverage target. Overall, these findings highlight gaps in training, service delivery, and community awareness that must be addressed to improve coverage and prevent future outbreaks. The MR supplemental immunization program in Palu City should be strengthened by ensuring annual training for immunization officers, enforcing complete SOP documentation, including vaccine stock and logistics recording, and implementing targeted outreach to improve coverage in CHCs that failed to meet the 100% target.